A novel method for beef bone protein extraction by lipase-pretreatment and its application in the Maillard reaction. (1st October 2016) - Song, Shiqing; Li, Sisi; Fan, Li; Hayat, Khizar; Xiao, Zuobing; Chen, Lihua; Tang, Qi
Highlights: A procedure was set up to produce extract from beef bone by lipase pretreatment. An excellent beef aroma was formed due to plentiful amino acids in the extract. Industrial beef by-product was used to produce food flavouring by Maillard reaction. Abstract: Five beef bone hydrolysates were obtained by different enzyme treatment schemes, including papain (M), combination of porcine pancreatic lipase and papain (Z + M, combination of lipase and papain (Y + M), Protamex (F), combination of porcine pancreatic lipase and Protamex (Z + F). The degree of hydrolysis (DH), free amino acids and molecular weight distribution of these hydrolysates were evaluated. To further explore the differences between these five hydrolysates, Maillard reaction products (MRPs) were prepared using a xylose/cysteine/hydrolysate model. It was found that the DH, content of low molecular weight peptides and amino acids of hydrolysates increased significantly after lipase pre-treatment. GC–MS showed that the total content of furans, pyrroles and thioethers in MRPs Y + M increased by 78.0% compared with MRPs M, while in MRPs Z + F, pyrazines increased by 44.1% compared with MRPs F. Examining the sensory characteristics of the MRPs, the MRP from the hydrolysate of Y + M had the best mouthful, umami and meaty characteristics. The correlation analysis further confirmed that an appropriate lipase pre-treatment could improve the flavour of MRPs.